Price changes in Finland: some evidence from micro CPI data. - Samu Kurri (European Central Bank (ECB), 2007)
In this paper we analyse the Finnish consumer price changes from February 1997 to December 2004 on the basis of a set of microdata which covers over half of the items included in the Finnish CPI. Our findings can be summarised with four stylised facts. Firstly, only a small fraction of prices change monthly. In the period under review, an average 80% of prices remained unchanged in consecutive months. Secondly, price changes can be large in both directions. Thirdly, positive inflation is due to the higher number of price increases compared to decreases, and the magnitude of price changes is more or less in balance. Finally, the decomposition of monthly inflation to the weighted fraction of products with price changes and the weighted average of those price changes seems to give support for the time-dependent modelling of Finnish consumer prices, although signs of state-dependent pricing can also be found in the data.
Keywords: E31; D40; L11; 330; consumer prices; rigidity; state-dependent pricing; time-dependent pricing; Verbraucherpreisindex; Preisrigidität; Finnland